2011
DOI: 10.1200/jco.2010.31.6760
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in Patients With Sentinel Node–Positive Melanoma Is Accurately Defined by the Combined Rotterdam Tumor Load and Dewar Topography Criteria

Abstract: Patients with metastases < 0.1 mm, especially when present in the subcapsular area only, may be overtreated by a routine CLND and have an MSS that is indistinguishable from that of SN-negative patients. Thus the RDC criteria provide a rational basis for decision making in the absence of conclusions provided by randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
1
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(90 citation statements)
references
References 50 publications
7
71
1
10
Order By: Relevance
“…According to published data, a combination of various parameters of tumor load and location of the micrometastasis provides the best potential for gauging involvement of N-SLN. When considering both size criteria and Dewar classification, a group of subcapsular metastases < 0.1 mm was identified at very low risk (2 %) for positive N-SLN [213]. In a retrospective analysis of patients with the lowest scores, the "Hannover system" [193], developed from [190]), which is based on the combination of maximum diameter of metastases (cut-off 0.1 mm), TPD (tumor penetrative depth, cut-off 2 mm) and capsular infiltration (present/not present), yielded overall and recurrence-free survival rates similar to SLNnegative patients.…”
Section: B Frerichmentioning
confidence: 99%
See 4 more Smart Citations
“…According to published data, a combination of various parameters of tumor load and location of the micrometastasis provides the best potential for gauging involvement of N-SLN. When considering both size criteria and Dewar classification, a group of subcapsular metastases < 0.1 mm was identified at very low risk (2 %) for positive N-SLN [213]. In a retrospective analysis of patients with the lowest scores, the "Hannover system" [193], developed from [190]), which is based on the combination of maximum diameter of metastases (cut-off 0.1 mm), TPD (tumor penetrative depth, cut-off 2 mm) and capsular infiltration (present/not present), yielded overall and recurrence-free survival rates similar to SLNnegative patients.…”
Section: B Frerichmentioning
confidence: 99%
“…Besides the length of the largest tumor cluster (limit value 0.1 mm), another study revealed the anatomic location according to Dewar as prognostic factor [213].…”
Section: Level Of Evidence 2bmentioning
confidence: 99%
See 3 more Smart Citations